Controlling the Formation of Sodium/Black Phosphorus IntercalationCompounds Towards High Sodium Content - Werbach, Katharina; Neiß, Christian; Muellner, Alexander; Abellan, Gonzalo; Setman, Daria; Lloret, Vicent; Wild, Stefan; Hauke, Frank; Pichler, Thomas; Hirsch, Andreas; Peterlik, Herwig (Batteries & Supercaps, 2021)
The solid-state synthesis of pure sodium-black phosphorus intercalation compounds (Na-BPICs) has been optimized in bulk for two stoichiometric ratios. Specifically, in-situ X-Ray diffraction (XRD) allowed the precise identification of the optimal temperature range for the formation of Na-BPICs: 94 degrees C-96 degrees C. Moreover, as the undesired formation of Na3P takes place at this very same range, we succeeded in introducing a new synthetic route based on a fast-thermal ball milling implementation that results in the bulk production of BPIC without Na3P in 9 out of 10 cases. Finally, by combining XRD, Raman spectroscopy, and DFT calculations we developed a new structural model for Na-based BPICs showing an increase of BP's unit cell with Na atoms incorporated in every second layer. These results will pave the way for the large-scale synthesis and application of pure BPICs, which are of great interest in fields such as optoelectronics or energy storage.
CRIS-Team WoS Importer:2021-04-23